PENERAPAN KONSEP HARGA OBAT DAN ETIKA PELAKU BISNIS MENURUT PERSPEKTIF ISLAM DI APOTEK - Erki Arfianto; risda hayati; Zamal Daud Dandhy; Indriyati Hadi Sulistyaningrum (JOURNAL OF PHARMACEUTICAL (JOP), 2026)
Pharmaceutical services are essential in guaranteeing the availability of medicines that are safe, effective, and affordable. Nevertheless, in real practice, the pharmaceutical sector is often influenced by profit-oriented pricing strategies that may contradict ethical principles. This study aimed to assess the compliance of oral generic drug prices with the government’s Maximum Retail Price (MRP) policy and to analyze the integration of Islamic business ethics in pharmacy services at Waras Barokah Pharmacy. The research employed a descriptive qualitative and non-experimental quantitative design. Quantitative data were collected from 60 samples of oral generic drugs and analyzed by comparing Pharmacy Selling Prices (PSP) with MRP using Microsoft Excel. Qualitative data were obtained through interviews, observations, and document reviews, and further analyzed based on the four Islamic ethical values: Siddiq (honesty), Amanah (trustworthiness), Tabligh (transparency), and Fathanah (wisdom). Results showed that most generic drug prices were within the MRP threshold and the pharmacy consistently applied Islamic ethical principles. In conclusion, Waras Barokah Pharmacy demonstrates successful integration of regulatory compliance and Islamic ethics, offering a replicable model of shariah-compliant pharmaceutical practice.